A Contrastive Study Of Culture- Specific Concepts In English and Uzbek Proverbs - Saitkulova, Munisa Shokirovna; Kambarova, Marzhan Adil qizi (The Lingua Spectrum, 2026)
This research is concerned with the contrastive analysis of English and Uzbek proverbs as a linguistic and cultural phenomenon, aiming to identify their universal and nationally specific features. This study focuses on the interaction between language, culture and human cognition, conducted within the framework of Linguistics, Modern linguistics and Cognitive linguistics. The research is based on qualitative methods and comparative analysis of English and Uzbek proverbs. A contrastive analysis of Uzbek and English proverbs shows that although proverbs have general cognitive basis, they represent different national worldview. The results show that proverbs are one of the notions that represent culture and human experience which are shaped by social and historical development. The finding plays crucial role in conceptualization which is significant in Linguistics, Modern linguistics and Comparative linguistics providing both theoretical and practical examples for further researches. This study also contributes to intercultural communication and helps to understand different ways of thinking between cultures.